2017
DOI: 10.3390/met7100411
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Ag Leaching from Arsenic Sulfosalts in the S2O32−-O2-NaOH System

Abstract: Abstract:In Zimapan, Mexico abundant mineral species have been identified. However, a significant number of these precious metals appear to be related to complex sulfides, as is the case of silver (Ag) in sulfosalts. In this work, a kinetic study of the formation of Ag complexes in the AgAsS 2 -S 2 O 3 2− -O 2 -NaOH system from a Zn concentrate found in the Zimapan mining district was conducted. The kinetic model application on Ag leaching shows a linear adjustment in the valuation of the particle size effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…As the pH value in a solution decreases, the Au and Ag ions form a complex with anions, and their predominant species have a negative charge. [ 32 ] At pH values below 2, the surface charge of the N‐MXene nanosheet stack becomes more positive and adsorbed the heteropolar Au‐ and Ag‐anion complexes. Remarkably, the high recovery performance of the N‐MXene nanosheet stack for Au and Ag ions in strongly acidic conditions is very advantageous in terms of practical application because most leachates for extracting metal ions from e‐waste make the solution strongly acid.…”
Section: Resultsmentioning
confidence: 99%
“…As the pH value in a solution decreases, the Au and Ag ions form a complex with anions, and their predominant species have a negative charge. [ 32 ] At pH values below 2, the surface charge of the N‐MXene nanosheet stack becomes more positive and adsorbed the heteropolar Au‐ and Ag‐anion complexes. Remarkably, the high recovery performance of the N‐MXene nanosheet stack for Au and Ag ions in strongly acidic conditions is very advantageous in terms of practical application because most leachates for extracting metal ions from e‐waste make the solution strongly acid.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in the literature 21,22 that in the presence of thiosulfate, the standard potential of Ag + /Ag is reduced from 0.80 to 0.01 V. Therefore, Ag can be oxidized to Ag + by dissolved O 2 and form Ag(S 2 O 3 ) 2 3− complexes. Ruiz et al 23 showed fast dissolution of Ag (less than 20 min) at neutral pH and formation of two complexes: Ag(S 2 O 3 ) 3 5− (predominant species) and Ag(S 2 O 3 ) 2 3− . Due to such behaviour thiosulfates were even used for leaching of silver from sulfurous minerals.…”
Section: Development Of the Hplc-icp-ms Methods For Speciation Analys...mentioning
confidence: 99%
“…It has a total volume of 14.3 million tons, produced in three technologically different periods: grinding-amalgamation, followed by grinding-cyanidation and grinding-flotation-cyanidation [27]. The samples were digested with aqua regia and analyzed using Perkin Elmer Optima 3200 RL ICP-OES spectrometer in order to identify and quantify the elements present in the mine dumps.…”
Section: Methodsmentioning
confidence: 99%
“…01-074-3485), representing the mineralization matrix of these mining residues [27]. Ag appears to be absent in the diffractogram because silver concentration in the residues is under the detection limit of this technique.…”
Section: Mineralogical Characterizationmentioning
confidence: 99%